Implementasi Model Pembelajaran STAD Berbantuan LKM Untuk Meningkatkan Hasil Belajar Akuntansi Sektor Publik - Irianto, Okto (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2019)
This study aims to determine the improvement of student learning outcomes through the implementation of STAD learning model assisted with LKM. This study was a Classroom Action Research (CAR) which was conducted in 3 cycles. Time of study in odd semester Academic Year 2018/2019, with a sample of accounting students at the Faculty of Economics and Business, University of Musamus, Merauke. The data analysis technique in this study is descriptive quantitative data analysis with percentages. The results of the study show that the Implementation of STAD Learning Model Assisted with LKM can improve Public Sector Accounting Learning Outcomes. The increase can be seen from the average value of student learning outcomes on the cycle of 50,36, increasing in the first cycle of 61,02, increasing in the second cycle of  73.07, and increasing in the third cycle of 85,31.